The governance of Muriaé’s (MG) clothing local production arrangement based on a bidimensional model analysis - Antero, Cecilia Alves da Silva; Tavares, Bruno; Antonialli, Luiz Marcelo; Castro, Sabrina Olimpio de Caldas (Revista de Administração da UFSM, 2019)
The aim of this study was to understand governance in Muriaé’s (MG) clothing LPA. A qualitative study of descriptive character, supported by case study method, was performed. Additionally, an analytical model for analysis of governance in LPA was proposed based on the following categories: representation, cooperation and coordination. The primary qualitative data were analyzed with support of the NVIVO® software, using the content analysis technique. Governance in the clothing LPA of Muriaé-MG is characterized by expressive representation of the actors, the incipient cooperation and coordination of the companies and the significant operations of most entities that are committed to the development of said LPA. This study expanded the understanding of the theme of governance in LPA due to its detailed consideration of the criteria used for their understanding, regarding the procedures that can be employed to conduct an investigation, which may be adopted in future researches.